1985
DOI: 10.1037/0022-3514.48.6.1413
|View full text |Cite
|
Sign up to set email alerts
|

The influence of positive affect on the unusualness of word associations.

Abstract: A pilot study and two experiments investigated the influence of positive affect, induced in three differing ways, on the uniqueness of word associations. Persons in the positive-affect conditions gave more unusual first-associates to neutral words, according to the Palermo & Jenkins (1964) norms, than did subjects in the control conditions. In Study 3, where word type (positive, neutral, negative) was a second factor along with affect, in a between-subjects design, associates to positive words were also more u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
439
1
18

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 629 publications
(488 citation statements)
references
References 33 publications
25
439
1
18
Order By: Relevance
“…The influence of positive affect on speed of responding to negative adjectives also may be accounted for by this perspective, if we assume that positive affect increases the perceived similarity of negative adjectives. This position is entirely consistent with Isen's findings that positive affect enables individuals to generate more unusual and diverse first associates to words as well as to increase the flexibility of categorization of material (Dovidio et al 1995;Isen et al 1985;Kahn and Isen 1983). All of these processing effects may serve to increase similarity among negative adjectives, which in turn may increase their accessibility.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The influence of positive affect on speed of responding to negative adjectives also may be accounted for by this perspective, if we assume that positive affect increases the perceived similarity of negative adjectives. This position is entirely consistent with Isen's findings that positive affect enables individuals to generate more unusual and diverse first associates to words as well as to increase the flexibility of categorization of material (Dovidio et al 1995;Isen et al 1985;Kahn and Isen 1983). All of these processing effects may serve to increase similarity among negative adjectives, which in turn may increase their accessibility.…”
Section: Discussionsupporting
confidence: 77%
“…They demonstrate that positive affect enables people to generate more unusual and diverse first associates to neutral words (Isen et al 1985;Kahn and Isen 1993), to categorize objects more flexibly (Isen and Daubman 1984;Murray, Sujan, and Hirt 1990), to form broader consideration sets (Kahn and Isen 1993), to understand metaphors (Roehm and Sternthal 2001), to process systematically (Bless et al 1996), and to be better able to solve a wide range of problems (Amabile, Bersade, and Mueller 2005;Aspinwall 1998;Carnevale and Isen 1986;Erez and Isen 2002;Estrada, Isen, and Young 1997;Fredrickson 2001;Isen, Daubman, and Nowicki 1987;Isen, Rosenzweig, and Young 1991;Staw and Barsade 1993). Isen (2001, 77) summarizes a sizable literature by noting, "What the literature in the field now shows is that increased thinking, cognitive elaboration, is characteristic of positive affect, and that it does not, in fact, lead to depletion in cognitive capacity or depletion in motivation to process systematically."…”
mentioning
confidence: 99%
“…This task has been shown to manipulate mood state effectively (e.g., Isen, Johnson, Mertz, & Robinson, 1985). Participants' responses included associations such as satin and soft to the word smooth and table and wood to the word desk.…”
Section: Methodsmentioning
confidence: 99%
“…Hirt, Melton, McDonald, and Harackiewicz (1996) suggested that positive mood may enhance performance on creativity tasks yet impair performance on tasks requiring more detailed, systematic processing. In support of this distinction, positive mood reliably leads to more creativity in problem solving (e.g., Estrada, Young, & Isen, 1994;Greene & Noice, 1988;Isen, Daubman & Nowicki, 1987;Isen, Johnson, Mertz, & Robinson, 1985), improved integration of available information (e.g., Estrada, Isen, & Young, 1997), and more flexible classification of material (e.g., Isen & Daubman, 1984;Isen, Niedenthal, & Cantor, 1992;Kahn & Isen, 1993). By contrast, in a wide range of tasks requiring more systematic information processing, positive affect results in a simplification of the task and diminished judgmental quality (e.g., Isen & Means, 1983;Sinclair, 1988).…”
Section: Processing Effects Of Transient and Enduring Affectmentioning
confidence: 99%